A study on the decision making process in newsrooms and government policies under Dato’ Sri Mohd Najib’s Administration: a Comparison between RTM and AstroAwani - Roslina Abdul Latif; Faridah Ibrahim (Universiti Kebangsaan Malaysian, 2012)
Most journalism is not about facts but about the interpretation of what seem to be facts. In recent years, the interpretation, influence and pervasiveness of the news from different media organisation are beyond doubt. Yet there are still disagreements and conflicting views about just how the public is influenced by the media in general by the news written by the journalist in particular and the stories produced by the editors specifically. Journalism is often called the news business – the gathering, the processing and delivery of important and interesting information and further developments or follow-up stories by newspapers and broadcast media or vice versa – is inextricably entangled in that giant, whirling entity often referred to as the media. Story selection is a decision-making and choice-making process but a hurried one. As a result, the considerations must be quickly and easily applicable so that choices can be made without too much deliberation. Notable editors, chief editors and group editors gave in-depth interviews on their decision making process and issues of internal and external forces that ‘dampen’ the process of nation building in shaping the trajectory of the news,hence, sustaining a potentially transformative public sphere in tandem with the prime minister’s elaborate government policies.